Analysis of the Use of Digital Media in Online Learning for Down Syndrome Students during the COVID-19 Pandemic - Nurjanah, Sarah Anisa; Ayuningtyas, Fitria (PLD UIN Sunan Kalijaga, 2024)
In connection with the Ministry of Education and Culture of Circular Letter Number 4 of 2020 regarding the COVID-19 pandemic, which requires distance learning, has a significant impact on teachers and students pandemic; with Down syndrome who also have to carry out the learning process online without face-to-face meetings. This research uses descriptive qualitative methods to know how digital media is utilized by teachers and students with Down syndrome and how it impacts children with Down syndrome after using digital media continuously. This research indicates that digital media is used not only for academic learning but also non-academic such as extracurriculars, to train children's creativity and creation. As for the impact of digital media, the informants acknowledged that changes in their children's behavior and emotions were influenced by what they watched. Therefore, it is necessary to have strict supervision and attention from parents/caregivers regarding the use of digital media and their children's viewing. Sehubungan dengan Surat Edaran Mendikbud Nomor 4 Tahun 2020 tentang situasi pandemi COVID-19 yang mengharuskan dilakukannya pembelajaran jarak jauh, hal ini berdampak besar bagi guru dan siswa dengan down syndrome yang juga harus melakukan proses pembelajaran secara daring tanpa bertatap muka secara langsung. Penelitian ini menggunakan metode kualitatif deskriptif dengan tujuan untuk mengetahui bagaimana media digital dimanfaatkan oleh para guru dan siswa dengan down syndrome serta bagaimana dampaknya kepada anak-anak dengan down syndrome setelah menggunakan media digital secara terus menerus. Penelitian ini menunjukkan bahwa media digital dimanfaatkan bukan hanya sebagai pembelajaran akademik saja melainkan juga non-akademik seperti ekstrakurikuler untuk melatih kreativitas dan kreasi anak. Adapun dampak media digital itu sendiri para informan mengakui adanya perubahan pada perilaku dan emosi anak mereka yang dipengaruhi oleh tontonan mereka. Oleh karena itu, perlu adanya pengawasan dan perhatian yang ketat dari para orang tua terkait penggunaan media digital serta tontonan anak anak mereka.